Développer la pensée informatique à travers la conception de jeux vidéo éducatifs. Educational Game & Play Design Project: élaboration de la méthode - Jérémy Le Du; Julian Alvarez; Daniel Schmitt (Distances et Médiations des Savoirs)
Video games are becoming an increasingly important part of children’s daily leisure activities. Their use as an educational tool seems to be a good way to combat the decline in motivation and the loss of meaning in learning that has been observed among students. The constructionist approach proposed by Papert aims to explore the creation of video games by learners. Several studies have shown that it is associated with the development of computational thinking. However, a recent meta-analysis has tempered these conclusions due to a lack of relevant quantitative evidence (Denner et al., 2019). This article aims to identify the optimal way to integrate video game design activities in French schools, with a view to developing computational thinking. Based on a literature review and a test phase carried out with a group of 50 students, an experimental research programme has been developed: the “Educational Game & Play Design Project.” It has been offered to dozens of French schools since the start of the 2022 school year. Its aim is to enable participating students to strengthen their 21st century skills, starting with computational thinking.